Policy Making Model in Flood Disaster Management in West Aceh - Yeni Sri Lestari; Irma Juraida; Dara Quthni Effida (Pencerah, 2021)
This article examines various government policy issues that often intersect with the interests of many people,even though policy is the main foundation in upholding integration between government, society and welfare. Thevarious policy processes that exist indicate that each policy must be formulated appropriately to create synergybetween inputs and outputs. This also applies to flood prevention in West Aceh. Therefore, this study will examinehow the existing policy models in West Aceh in dealing with floods? And how is the effectiveness of the policy inovercoming the flood disaster in West Aceh? This study is described using a qualitative descriptive approach andliterature study as the research method of this study. Some policies in West Aceh consist of policies made usingthe rational model and also the incremental model. In addition, the study found that the policy model for dealingwith floods in Aceh Barat has not had a positive impact on the annual flood mitigation that always occurs.